Odpowiedzi

2010-03-01T21:25:50+01:00
5x + y = 9 / * (-3)
2x + 3y = 1


-15x - 3y = -27
+ 2x + 3y = 1
___________________________

-13x = -26
x = 2


Liczę na naj. ; ] mam nadzieje, ze pomogłam.
Najlepsza Odpowiedź!
2010-03-01T21:26:04+01:00
5x+y=9
2x+3y=1

y=9-5x
2x+3*(9-5x)=1

y=9-5x
-13x=-26 /:(-13)

y=9-5x
x=2

y=-1
x=2

Odp. Rozwiązaniem układu równań jest para liczb x=2 i y=-1.
2010-03-01T21:28:28+01:00
5x+y=9/* (-3)
2x+3y=1/*1
-15x+-3y=-27
2x+3y=1
-13x=-26/:(-13)
x=2
4+3y=1
3y=1-4
3y=3/:-3
y=-1
x=2
y=-1
pozdrawiam ;))